Correlation between Time Variation of Steam Distillation of Temu Hitam’s Rhizomes (Curcuma aeruginosa) and Antibacterial Activity of Essential Oil - Munawaroh, Fauziyatul; Luthfiana, Widya; Suparto, Irma Herawati; Sari, Yessie Widya; Wahyuni, Wulan Tri; Batubara, Irmanida (Jurnal Jamu Indonesia, 2023)
Distillation time can affect the extraction of essential oils such as the rhizome of temu hitam (Curcuma aeruginosa) which has been shown to have antibacterial activity. Therefore, this study aims to determine the optimum distillation time to produce temu hitam rhizome oil with the strongest antibacterial activity. The rhizomes of temu hitam were steam distilled with different length of time every 30 minutes for 4 hours to obtain essential oil and determined the compounds contained in them using gas chromatography-mass spectrometry. Antibacterial activity was determined by disc diffusion against Streptococcus mutans, Escherichia coli, and Staphylococcus aureus. The most dominant compounds present in essential oils are eucalyptol (34.89%), epicurzerenone (20.58%), and camphor (16.90%) based on the average peak of the total distillation time. The strongest antibacterial potency was obtained in the first 30 minutes of distillation for S. mutans and E. coli, and in the seventh 30 minutes of distillation for S. aureus.